2018
DOI: 10.1242/jcs.216382
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive adhesion systems mediate glioma cell invasion in complex environments

Abstract: Diffuse brain invasion by glioma cells prevents effective surgical or molecular-targeted therapy and underlies a detrimental outcome. Migrating glioma cells are guided by complex anatomical brain structures but the exact mechanisms remain poorly defined. To identify adhesion receptor systems and matrix structures supporting glioma cell invasion into brain-like environments we used 2D and 3D organotypic invasion assays in combination with antibody-, peptide- and RNA-based interference. Combined interference wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…The development of glioma is a complex biological process that involves multiple mechanisms and factors (10,11). Numerous tumor suppressor genes, oncogenes, and growth factors have been confirmed to be involved in glioma progression (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The development of glioma is a complex biological process that involves multiple mechanisms and factors (10,11). Numerous tumor suppressor genes, oncogenes, and growth factors have been confirmed to be involved in glioma progression (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The mode of migration may be critical for how well tumor cells, including those in GBM, are able to invade the surrounding tissue and disseminate. Several recent studies found that GBM cells can migrate collectively 26,27 , although whether GBM CSCs specifically use this type of migration is an open question. Our data indicate that a variety of patient-derived GBM CSC models can move in small to large collectives away from tumor spheres plated on Geltrex, although CSCs can also migrate individually and as mixtures of single cells and collectives.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of U87 cells to cilengitide-induced detachment has been shown to be dependent on the composition of the ECM, with cells cultured on collagen-coated plates resisting detachment (34,46). Gritsenko and Friedl have recently demonstrated that αV and β1 integrins represent the primary adhesion systems for glioma cell migration in different migration models (spheroids and organotypic brain slices) (35). However, P R E P R I N T when they compared the same integrin interference strategy in the different models, they observed a variation in the contribution of integrin-dependent glioma invasion.…”
Section: Drug Effects On Cell Invasion Versus Cell Migrationmentioning
confidence: 99%